On the use of bilogical parameters in prediction of response to high dose chemotherapy in breast, ovarian and small cell lung cancers - Lange, Andrzej; Dłubek, Danuta; Gryboś, Marian; Klimczak, Aleksandra; Kryczek, Ilona (Contemporary Oncology/Współczesna Onkologia, 2000)
High dose chemotherapy in solid tumors is still at the experimental phase. Response to the therapy largely depends on the stage, possibilities of surgical intervention and sensitivity to chemotherapy. Biological characteristics of a tumour may help in choosing the optimal modality of the treatment. Immunochemistry of tumour sections helps to evaluate: 1) rate of proliferation (Ki67+); 2) accumulation of p53, which reflects mutation this gene; 3) lymphocyte infiltration characteristics. This data supplemented with the evaluation of the overexpression of Her2-neu in breast cancer provides with some information, which may help in treatment response prediction. Similarly, in ovarian carcinoma and small cell lung carcinoma thorough description of tumours in patients undergoing HD chemotherapy helps to verify hypothesis on the value of biological tumor description in prediction of the response to the therapy.